Investigation of micromachined antenna substrates operating at 5 GHz for RF energy harvesting applications - Yunus N.H.M.; Yunas J.; Pawi A.; Rhazali Z.A.; Sampe J. (MDPI AG, 2023)
Bandwidth; CMOS integrated circuits; Electric rectifiers; Energy harvesting; Glass; MEMS; Metals; Microstrip antennas; Microwave antennas; MOS devices; Omnidirectional antennas; Oxide semiconductors; Permittivity; Rectennas; Silicon; Slot antennas; Substrates; Surface micromachining; Antenna gains; Dielectric permittivities; ISM bands; Micromachined antenna; Rf energy harvesters; RT/Duroid 5880; Directional patterns (antenna)